Formalne, pozaformalne i nieformalne aspekty zdobywania wiedzy przez internet – próba modelowego ujęcia - Wilczek, Marcin (Ogrody Nauk i Sztuk, 2017)
Internet jest miejscem, w którym dynamicznie rozwijają się nowe formy edukacji. Korzystanie z jego zasobów nie jest już przywilejem, a powoli staje się koniecznością we współczesnym świecie. Artykuł jest próbą modelowego ujęcia obszarów edukacji formalnej, nieformalnej i pozaformalnej obecnych w dobie cyfryzacji. Formal, non-formal and informal aspects of acquiring knowledge through the internet – an attempt at a model description Abstract The Internet is a place where new forms of education are dynamically developing. Use of its resources is no longer a privilege, it is slowly becoming a necessity in the modern world. This article is an attempt to describe a model of the formal, informal and non-formal education areas prevalent in the age of digitization. Key words: internet, lifelong learning, self-education, teacher, e-learning